Water extraction and root traits in Oryza sativa x Oryza glaberrima introgression lines under different soil moisture regimes - Kijoji, Abubakary A.; Nchimbi-Msolla, Susan; Kanyeka, Zakaria L.; Klassen, Stephen P.; Serraj, Rachid; Henry, Amelia (Commonwealth Scientific and Industrial Research Organisation, 2013)
Drought is a major constraint to rainfed rice production in some parts of sub Saharan Africa (SSA) because of irregular and low rainfall. Improving root water uptake during progressive soil drying could contribute to terminal drought stress resistance. Two lysimeter experiments were conducted using 200 introgression lines (ILs) derived from Oryza sativa L. × Oryza glaberrima Steud. crosses (IR64/RAM54 and IR64/RAM90) to characterise water uptake and root traits under progressive soil drying and to assess genetic differences among these lines in relation to drought stress. The lysimeter facility setup and protocols for simultaneous monitoring of water uptake rates and leaf area are described. Significant genetic variability for water uptake and root traits among the ILs was observed under drought stress. Water uptake in the drought stress treatments was correlated with root length density (RLD) and root dry matter (RDM) at lower soil depths. The highest RLD values at depth were observed among the RAM90 ILs and genetic differences were observed between RAM90 and RAM54 populations, implying that accession RAM90 could be used as a source for improving drought avoidance in lowland rice. The ILs with greater water uptake identified in this study will be used in future research for improving drought resistance of rice in SSA.